2014
DOI: 10.1021/jf503922h
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Wine Polymeric Pigments Formed from Anthocyanin and Tannins Differing in Size Distribution and Subunit Composition

Abstract: To explore the effect of tannin composition on pigment formation, model ferments of purified 3-O-monoglucoside anthocyanins (ACN) were conducted either alone or in the presence of two different tannins. Tannins were isolated from grape seeds (Sd) or skins (Sk) following exhaustive extraction in 70% v/v acetone. The Sd and Sk tannin fractions had a mean degree of polymerization of 5.2 and 25.6, respectively. The Sd fraction was highly galloylated, at 22%, but galloylation was <2% in the Sk fraction. The Sk frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 50 publications
5
27
0
Order By: Relevance
“…The oligomers formed by anthocyanins via ethyl bridges were detected in PW-A200 (Figure 2b), and the extracted ion of m/z 923 exhibited fragment ions at m/z 761, 599, 476, 448, and 314. The fragment ions at 761 were resulted from neutral loss of the glucose moiety (−162 u), while m/z 476 and 448 were derived from the cleavage of the C-3-G with or without ethyl-bridge which had been confirmed previously (Bindon et al, 2014). Furthermore, the consecutive loss of two glucoside moieties (−162 u) was also observed among m/z 923, 761, and 599.…”
Section: Characterization Of Nonbleachable Pigments Of Reaction Mixturessupporting
confidence: 73%
“…The oligomers formed by anthocyanins via ethyl bridges were detected in PW-A200 (Figure 2b), and the extracted ion of m/z 923 exhibited fragment ions at m/z 761, 599, 476, 448, and 314. The fragment ions at 761 were resulted from neutral loss of the glucose moiety (−162 u), while m/z 476 and 448 were derived from the cleavage of the C-3-G with or without ethyl-bridge which had been confirmed previously (Bindon et al, 2014). Furthermore, the consecutive loss of two glucoside moieties (−162 u) was also observed among m/z 923, 761, and 599.…”
Section: Characterization Of Nonbleachable Pigments Of Reaction Mixturessupporting
confidence: 73%
“…Previous studies even showed that the T/A ratio affected the production of polymeric pigments during bottle aging (Gambuti et al, 2017 ) and after a strong oxidation of red wine (Picariello et al, 2017 ). The composition of grape native tannins (Bindon et al, 2014 ) and the level of marc pressing and related release-diffusion of phenolics to medium (Gambuti et al, 2004 ; Cerpa-Calderón and Kennedy, 2008 ; Setford et al, 2017 ) are others crucial factors that significantly influence the formation of polymeric pigments in wines.…”
Section: Discussionmentioning
confidence: 99%
“…The mass concentration of phenolic and coloring substances in the clones of Cabernet-Sauvignon, Merlot and Bastardo Magarachsky exceeded those of traditional varieties. In general, the value of these indicators of all studied wine materials corresponded to the values typical for the Western European ecological-geographical group [5][6][7][8][9][10][11][12][13][14][15]. Tasting assessments of the studied wine materials are presented in Figure 1.…”
Section: Resultsmentioning
confidence: 58%